2024
DOI: 10.3390/v16030359
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profile of Variants Potentially Associated with Severe Forms of COVID-19 in Amazonian Indigenous Populations

Rita de Cássia Calderaro Coelho,
Carlliane Lima e Lins Pinto Martins,
Lucas Favacho Pastana
et al.

Abstract: Coronavirus disease 2019 (COVID-19) is an infection caused by SARS-CoV-2. Genome-wide association studies (GWASs) have suggested a strong association of genetic factors with the severity of the disease. However, many of these studies have been completed in European populations, and little is known about the genetic variability of indigenous peoples’ underlying infection by SARS-CoV-2. The objective of the study is to investigate genetic variants present in the genes AQP3, ARHGAP27, ELF5L, IFNAR2, LIMD1, OAS1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Previous research also found mitigating differences between the genetic profile of indigenous peoples and those of the other five world populations examined here [60][61][62]. However, the physical and geographic isolation of these peoples contributes to a gap in epidemiologic and genetic information.…”
Section: Discussionmentioning
confidence: 48%
“…Previous research also found mitigating differences between the genetic profile of indigenous peoples and those of the other five world populations examined here [60][61][62]. However, the physical and geographic isolation of these peoples contributes to a gap in epidemiologic and genetic information.…”
Section: Discussionmentioning
confidence: 48%